A cost-effectiveness and safety analysis of dual antiplatelet therapy comparing aspirin–clopidogrel to aspirin–ticagrelor in patients with acute coronary syndrome (Faculty of Medicine Universitas Indonesia, 2018)
Background: Dual antiplatelet therapy (DAPT) using either an aspirin–clopidogrel (A–C) combination or aspirin–ticagrelor (A–T) combination has become the standard therapy for acute coronary syndrome (ACS). Ticagrelor shows better pharmacokinetic profiles but is more expensive. This study aimed to compare cost-effectiveness and safety profiles of A–C versus A–T in patients with ACS. Methods: This was a retrospective cohort study of ACS patient at the Cipto Mangunkusumo Hospital between 2014 and 2016. ACS patients treated for the first time with A–T or A–C were included. Occurrence of major adverse cardiovascular events (MACE) within 3, 6, 9, and 12 months were used as effectiveness outcomes, while safety outcomes were measured based on the incidence of adverse drug reactions (major and minor bleeding, dyspnea, and hyperuricemia). Cost-effectiveness analysis was presented as incremental cost-effectiveness ratio (ICER). Results: Data records obtained from 123 ACS patients treated with A–C and 57 ACS patients treated with A–T were evaluated. Within the first three months, the MACE rate was 15.8% in the A–T group and 31.7% in the A–C group (RR: 0.498, 95% CI: 0.259–0.957, p=0.039). There was no statistically significant difference observed in the number of MACE between groups after 6, 9, and 12 months. The A–T group had a higher incidence of major bleeding (melena) than the A–C group (5.3% vs 1.62%, p=0.681), especially in geriatric patients. Minor bleeding was observed in three patients of the A–C group, but in none of the patients in the A–T group. The cost of ICER was IDR 279,438, indicating the additional cost needed for avoiding MACE within 3 months, if A–T was used. Conclusion: The aspirin–ticagrelor combination is a clinically superior and cost-effective option for MACE prevention among ACS patients, especially during the first three months of DAPT, with a slight but not significantly higher major bleeding risk when compared to the aspirin–clopidogrel combination.